Digitally‐enabled, patient‐centred care in rhinitis and asthma multimorbidity: The ARIA‐MASK‐air® approach. Issue 1 (7th January 2023) - Bousquet, Jean; Anto, Josep M.; Sousa‐Pinto, Bernardo; Czarlewski, Wienczyslawa; Bedbrook, Anna; Haahtela, Tari; Klimek, Ludger; Pfaar, Oliver; Kuna, Piotr; Kupczyk, Maciej; Regateiro, Frederico S.; Samolinski, Boleslaw; et al.
Abstract: MASK‐air ®, a validated mHealth app (Medical Device regulation Class IIa) has enabled large observational implementation studies in over 58, 000 people with allergic rhinitis and/or asthma. It can help to address unmet patient needs in rhinitis and asthma care. MASK‐air ® is a Good Practice of DG Santé on digitally‐enabled, patient‐centred care. It is also a candidate Good Practice of OECD (Organisation for Economic Co‐operation and Development). MASK‐air ® data has enabled novel phenotype discovery and characterisation, as well as novel insights into the management of allergic rhinitis. MASK‐air ® data show that most rhinitis patients (i) are not adherent and do not follow guidelines, (ii) use as‐needed treatment, (iii) do not take medication when they are well, (iv) increase their treatment based on symptoms and (v) do not use the recommended treatment. The data also show that control (symptoms, work productivity, educational performance) is not always improved by medications. A combined symptom‐medication score (ARIA‐EAACI‐CSMS) has been validated for clinical practice and trials. The implications of the novel MASK‐air ® results should lead to change management in rhinitis and asthma.